Pengaruh Model Problem Based Learning Dan Kecerdasan Emosional Terhadap Hasil Belajar IPA - Nurhidayati, Nurhidayati; Waluyo, Edy; Halqi, Muhammad (Educatio, 2024)
This research aims to determine whether there is an influence of the Problem Based Learning model with the Inquiry Learning model and emotional intelligence on the mathematics learning outcomes of class VI students at SD Negeri 1 Suka Damai for the 2024/2025 academic year. The approach used in this research is a quantitative approach with the research type being True Experimental Design, which is used to control all external variables that influence the course of the experiment. The population in this study was class VI students at SD Negeri 1 Suka Damai, totaling 40 students. Meanwhile, the sampling used in this research was a random sampling technique. Where the sample class is class VI A as an experimental class using the Problem Based Learning learning model and VI B as a control group using learning learning. After processing the data based on hypothesis testing, it shows that there are differences in the influence caused by Problem Based Learning and students' emotional intelligence on science learning. This is proven by the results of the hypothesis test, namely FA(count) = 25,214 and FA(table) = 4.01 where (25.214 ≥ 4.01) which means that Ha is accepted and Ho is rejected. Furthermore, there are interactions generated by the Problem Based Learning learning model on the science learning outcomes of class VI students at SD Negeri 1 Suka Damai for the 2024/2025 academic year. This can also be proven from the results of the hypothesis test, namely FAB(count) = 4.747 and FAB(table) = 4.01 where (4.747 ≥ 4.01) which means that Ha is accepted and Ho is rejected.